2001
DOI: 10.1257/aer.91.5.1221
|View full text |Cite
|
Sign up to set email alerts
|

Is the Price Level Determined by the Needs of Fiscal Solvency?

Abstract: The fiscal theory of price determination suggests that if primary surpluses evolve independently of government debt, the equilibrium price level "jumps" to assure fiscal solvency. In this non-Ricardian regime, fiscal policy--not monetary policy--provides the nominal anchor. Alternatively, in a Ricardian regime, primary surpluses are expected to respond to debt in a way that assures fiscal solvency, and the price level is determined in conventional ways. This paper argues that Ricardian regimes are as theoretic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
213
0
14

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 263 publications
(230 citation statements)
references
References 11 publications
3
213
0
14
Order By: Relevance
“…The first contributions, both of them for the case of the US economy, were those of Bohn (1998) and Canzoneri, Cumby and Diba (2001), who pioneered the two main approaches employed to test for the FTPL, namely, the so-called backward-looking and forwardlooking approaches, respectively. So, Bohn (1998) obtains, by means of econometric techniques, a positive response of the primary surplus-to-GDP ratio to the (lagged) debtto-GDP ratio.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first contributions, both of them for the case of the US economy, were those of Bohn (1998) and Canzoneri, Cumby and Diba (2001), who pioneered the two main approaches employed to test for the FTPL, namely, the so-called backward-looking and forwardlooking approaches, respectively. So, Bohn (1998) obtains, by means of econometric techniques, a positive response of the primary surplus-to-GDP ratio to the (lagged) debtto-GDP ratio.…”
Section: Introductionmentioning
confidence: 99%
“…So, Bohn (1998) obtains, by means of econometric techniques, a positive response of the primary surplus-to-GDP ratio to the (lagged) debtto-GDP ratio. In turn, making use of VAR analysis, Canzoneri, Cumby and Diba (2001) find that a positive innovation in the primary surplus would cause a fall in debt. Accordingly, the results of both studies would not support the existence of fiscal dominance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the major idea behind fitting additive models and we refer to Hastie & Tibshirani (1990) Table 3: Parametric estimates for model (2) using the data as shown in Figure 1 excluding 1916-1919 and 1940-1946. …”
Section: A Nonparametric Estimationmentioning
confidence: 99%
“…Formally, this was proven by Bohn (1998) assuming a constant reaction coefficient. Canzonerie et al (2001) generalized the proof by allowing for a time dependent reaction coefficient. 1 For the US, Bohn (1998) estimated OLS regressions and found that the primary surplus-GDP ratio is a positive function of the debt ratio implying that US debt policy is sustainable.…”
Section: Introductionmentioning
confidence: 99%